'Defending the family, ' safeguarding the nation: an examination of evangelical mobilisation in present-day Barbados. Issue 4 (2nd October 2018) - Lazarus, Latoya
ABSTRACT: This article addresses the connection between religion, culture and the family through a critical examination of evangelical Christians' focus on 'the family' in Barbados, in 2015 and 2016. The intentions are to highlight Evangelical Christians' strategic deployment of a common rhetoric or frame of 'defending the family, ' which was put forward in public discourses relating to sex, sexuality, marriage and the family. This rhetoric draws upon and reproduces deep-seated anxieties around the state of the family as well as its connection to ideas of progress, freedoms, national sovereignty and the establishment of strong nations. The article also sheds sociological light on Evangelical mobilisations by exploring the socio-cultural context in which they are occurring. The presented analysis is based on a critical feminist discourse analysis of relevant local and regional newspaper articles, blogs and websites, observational research as well as a review of secondary qualitative and quantitative data and pre-existing scholarly literature.